Dispersity-controlled ring-opening polymerization of epoxide - Yubo Zhou; Junpeng Zhao; Guangzhao Zhang (Nature Communications)
Abstract Dispersity or molar mass distribution (Ð M) profoundly influences polymer properties, but its control remains a challenge, especially for ring-opening polymerization (ROP). We report here a simple approach to tailor Ð M of aliphatic polyethers, e.g., poly(ethylene oxide) and poly(propylene oxide), by introducing an editable chain-transfer reaction in organocatalyzed ROP of epoxides. Trifluoroacetate, acting as the chain-transfer agent (CTA), brings about non-uniform growth of polyether chains while ensuring complete initiation efficiency and readily removable CTA residue. Triple control over Ð M (1.05–2.00), molar mass (3.6–17.7 kg mol−1), and end group is achieved simply by regulating the feed ratio, conforming well with the theoretical modeling. Experimental and calculation results reveal the orthogonality between chain growth and transesterification which is key to the three-modular ROP for independent Ð M control.